Strategi Manajemen Teaching Factory (TEFA) Berbasis Kemitraan Industri di SMK Ganesha Tama - Pradana, Dicky Tirta; Sutrisno, Valiant Lukad Perdana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2000)
The competency gap between vocational high school (SMK) graduates and industrial needs triggers high unemployment rates. Teaching Factory (TEFA) emerges as an innovative learning model to address this issue. This study aims to describe the TEFA management strategy implemented at SMK Ganesha Tama Boyolali. The research approach used is qualitative with a case study design. Data were obtained from eight informants through in-depth interviews, participant observation, and documentation studies. The data analysis technique followed an interactive model encompassing data reduction, data display, and conclusion drawing. The research results indicate that the TEFA management strategy is implemented through five main pillars: (1) strategic planning based on market analysis and curriculum synchronization with PT D-Tech Engineering; (2) strengthening partnerships through technical assistance and resource sharing; (3) functional organizational governance adopting corporate managerial structures (Production Manager, HRD, and GA); (4) operational implementation based on real orders (order-based) with a three-shift system ; and (5) a digitized monitoring system utilizing a geotagging attendance application. The integration of these five management pillars ensures the systemic relevance of vocational education to industrial standards.